2006
DOI: 10.1051/0004-6361:20054025
|View full text |Cite
|
Sign up to set email alerts
|

Structure and scaling of the entropy in nearby galaxy clusters

Abstract: Using XMM-Newton observations, we investigate the scaling and structural properties of the ICM entropy in a sample of 10 nearby (z < 0.2) morphologically relaxed galaxy clusters in the temperature range 2−9 keV. We derive the local entropy-temperature (S −T ) relation at R = 0.1, 0.2, 0.3 and 0.5R 200 . The logarithmic slope of the relation is the same within the 1σ error at all scaled radii. However, the intrinsic dispersion about the best fitting relation is significantly higher at 0.1R 200 . The slope is 0.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
146
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(182 citation statements)
references
References 42 publications
33
146
3
Order By: Relevance
“…Comparing to previous work, a wide variety of slopes have been found from fits to the entropy-temperature relation at 0.1 R 200 , ranging from very shallow (α = 0.49 ± 0.15: Pratt et al 2006; α = 0.50 ± 0.08: Nagai et al 2007) to very steep (α = 0.92 ± 0.12: Sanderson et al 2009; α = 0.85 ± 0.19: this work). We simply note that cool core-only samples tend to yield shallower slopes than statistically-selected samples, a fact borne out in the present data, for which the entropy temperature relation at 0.1 R 200 for the cool core subsample has a slope of α = 0.63 ± 0.94, while the morphologically disturbed subsample has a slope of α = 1.22 ± 0.76.…”
Section: Entropy Scaling Relationssupporting
confidence: 57%
See 1 more Smart Citation
“…Comparing to previous work, a wide variety of slopes have been found from fits to the entropy-temperature relation at 0.1 R 200 , ranging from very shallow (α = 0.49 ± 0.15: Pratt et al 2006; α = 0.50 ± 0.08: Nagai et al 2007) to very steep (α = 0.92 ± 0.12: Sanderson et al 2009; α = 0.85 ± 0.19: this work). We simply note that cool core-only samples tend to yield shallower slopes than statistically-selected samples, a fact borne out in the present data, for which the entropy temperature relation at 0.1 R 200 for the cool core subsample has a slope of α = 0.63 ± 0.94, while the morphologically disturbed subsample has a slope of α = 1.22 ± 0.76.…”
Section: Entropy Scaling Relationssupporting
confidence: 57%
“…Simulated profiles flatten in the very central regions due to entropy mixing (Wadsley et al 2008;Mitchell et al 2009). Observed profiles are also found generally to have similar external slopes (e.g., Pratt et al 2006;Sun et al 2009) and to flatten in the central regions in high Fig. 3.…”
Section: Radial Entropy Structurementioning
confidence: 67%
“…Markevitch et al 1998;Arnaud & Evrard 1999;Mohr & Evrard 1997;Finoguenov et al 2001;Ikebe et al 2002;Ponman et al 2003;Ettori et al 2004;Vikhlinin et al 2005;Pointecouteau et al 2005;Arnaud et al 2005;Pratt et al 2006;Kotov & Vikhlinin 2006;Zhang et al 2006;Maughan et al 2006;Maughan 2007;Arnaud et al 2007;Pratt et al 2009;Mantz et al 2010;Arnaud et al 2010;Sun et al 2011;Reichert et al 2011). An investigation of the relevant literature shows, however, that a number different methods are used for scaling the data at different redshifts.…”
Section: Introductionmentioning
confidence: 99%
“…Young et al 2011, and references therein). For example, star formation (galaxy feedback) is a suspected source of non-gravitational entropy excess (Buote et al 2007;Pratt et al 2006;Sun et al 2009), yet the amount of star formation required to reproduce the observed X-ray derived quantities (e.g. baryon fraction in gas or mass-temperature scaling relations) is at least ten times greater than the amount of stars observed (Gonzalez et al 2007;Kravtsov et al 2009;Andreon 2010).…”
Section: Introductionmentioning
confidence: 99%